TH1:x+1/2=0
x=-1/2
TH2:2/3-2x=0
2x=2/3-0
2x=2/3
x=1/3
x thuộc (-1/2 , 1/3)
`( x + 1 / 2 ) . ( 2 / 3 - 2x ) = 0`
`@TH1: x + 1 / 2 = 0`
`=> x = [-1] / 2`
`@TH2: 2 / 3 - 2x = 0`
`=> 2x = 2 / 3`
`=> x = 2 / 3 : 2`
`=> x = 1 / 3`
Vậy `x = 1 / 3` hoặc `x =[-1] / 2`
`(x + 1/2) . (2/3 - 2x) = 0`
$\\$
`<=>` `{(x + 1/2 = 0),(2/3 - 2x = 0):}`
$\\$
`<=>` `{(x = -1/2),(x = 1/3):}`
Vậy `x = {-1/2; 1/3}`
\(\Leftrightarrow\left[{}\begin{matrix}x+\dfrac{1}{2}=0\\\dfrac{2}{3}-2x=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{1}{2}\\-2x=-\dfrac{2}{3}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{1}{2}\\x=\dfrac{1}{3}\end{matrix}\right.\)
\(\left(x+\dfrac{1}{2}\right)\cdot\left(\dfrac{2}{3}-2x\right)=0\)
Th1 : \(x+\dfrac{1}{2}=0\)
\(x=0-\dfrac{1}{2}\)
\(x=-\dfrac{1}{2}\)
Th2 : \(\dfrac{2}{3}-2x=0\)
\(2x=\dfrac{2}{3}-0\)
\(2x=\dfrac{2}{3}\)
\(x=\dfrac{2}{3}:2\)
\(x=\dfrac{1}{3}\)
Vậy \(x=\left[{}\begin{matrix}-\dfrac{1}{2}\\\dfrac{1}{3}\end{matrix}\right.\)